Muhafidhah Novie* dan Zulifah Ch PENGARUH MEREK DAN STANDARDISASI MUTU TERHADAP DAYA SAING PRODUK MAKANAN BERBASIS UMKM DI SIDOARJO : Program Studi Manajemen, Universitas Nahdlatul Ulama Sidoarjo *e-mail: muhafidhahnovie.unusida@gmail.com - Muhafidhah Novie* dan Zulifah Chikmawati (GREENOMIKA, 2019)
The purpose of the study are to know Brand and Quality Standardization simulteanously and partiality to the Competitiveness of foods product base on UMKM. The reaserch method used quantitative methode, instrument testing with validity, reliability, normality, homoscedasticity and multicolinierity test. Incidental sampling with 50 food entrepreneur based on UMKM in Sidoarjo. Data analysis using SPSS program (Statistic Package for Social Science). The analysis result shows that there is a significant positive influence of variable X1 (Brand) and variable X2 (Quality Standardization) to variabel Y ( Competitiveness). Multiple linier equalition Y = 0,344 + 0,319X1 + 0,604X2. The result of regression test with F test that influence variable X1 and variable X2 simultaneous to variable Y is significant where the value of F arithmetic equal to 109.530 > Ftabel value that is 2.13. The effect of Quality Standardization is greater than Brand. This is need to be further reaserch on other factor that influence competitiveness such as innovation, technology and human resources.